If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 8) = 9x + 2 Reorder the terms: x(8 + x) = 9x + 2 (8 * x + x * x) = 9x + 2 (8x + x2) = 9x + 2 Reorder the terms: 8x + x2 = 2 + 9x Solving 8x + x2 = 2 + 9x Solving for variable 'x'. Reorder the terms: -2 + 8x + -9x + x2 = 2 + 9x + -2 + -9x Combine like terms: 8x + -9x = -1x -2 + -1x + x2 = 2 + 9x + -2 + -9x Reorder the terms: -2 + -1x + x2 = 2 + -2 + 9x + -9x Combine like terms: 2 + -2 = 0 -2 + -1x + x2 = 0 + 9x + -9x -2 + -1x + x2 = 9x + -9x Combine like terms: 9x + -9x = 0 -2 + -1x + x2 = 0 Factor a trinomial. (-1 + -1x)(2 + -1x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-1, 2}
| 6374738+267462626245= | | 8m-20=30 | | 3z^2+8z+6=9 | | (8x^4+9x^3-5)-(9x^2-2x+2)= | | -6x+6x-36=-36 | | -6+(1-5x)-(1-x)=2x-2(x-3) | | 10x+45=6 | | (9x^4+5x^3-4)-(7x^2-8x+5)= | | x^4+17x^2=0 | | 2x+50=3 | | 2/5y=4 | | .09x+.04x+56=490 | | (5x^4+8x^3-9)-(2x^2-5x+5)= | | y^2+169=0 | | (y-6)-(y+5)=8y | | [2.02]4(2x-3)=20 | | (4m^5+5m)-(-7m^5-6m+8)= | | -12+2y=-30 | | (8n^4+2n)-(-4n^4-4n+8)= | | 4x+2x-12=-30 | | 5x-2x(3x-7)=20 | | -42w=7 | | (2x^3-6x^2+6x)-(5x^2+4x+6)= | | 4w^2+40w=69 | | y^2-21y+0=0 | | (5x^3-2x^2+8x)-(9x^2+5x+3)= | | 5x^2+14x-21= | | (7x^3-4x^2+3x)-(7x^2+2x+3)= | | (8x^3-3x^2+7x)-(2x^2+5x+8)= | | (5x^3-9x^2+5x)-(4x^2+3x+6)= | | 23d+5=4(3d+5) | | (5x^2-2x-64)+(4x^2+8x)= |